1995
DOI: 10.1139/m95-064
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of pyrene and benzo[a]pyrene by nonbasidiomycete soil fungi

Abstract: The purpose of this study was to determine the ability of nonbasidiomycete soil fungi to oxidize pyrene (four rings) and benzo[a]pyrene (BaP) (five rings). Fungi were isolated from five different soils in which the polycyclic aromatic hydrocarbon content ranged from 0.8 to 80 micrograms/g dry soil. Approximately 50% of the isolates in all sites were able to oxidize pyrene. The pyrene-oxidizing species belonged to all fungal divisions except basidiomycetes. The most common were Penicillium spp. of the subgenus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 34 publications
1
47
0
1
Order By: Relevance
“…The compounds in peaks 2 and 3 were readily identified by their NMR patterns, which were both simplified because of the symmetry in the molecules. Furthermore, the NMR and UV spectra of peaks 2 and 3 matched those of 1,6 and 1,8 di-OH pyrene reported in the literature (62,63).…”
Section: Characterization Of Oxidation Products Of ␣Nf and Pyrene-supporting
confidence: 79%
“…The compounds in peaks 2 and 3 were readily identified by their NMR patterns, which were both simplified because of the symmetry in the molecules. Furthermore, the NMR and UV spectra of peaks 2 and 3 matched those of 1,6 and 1,8 di-OH pyrene reported in the literature (62,63).…”
Section: Characterization Of Oxidation Products Of ␣Nf and Pyrene-supporting
confidence: 79%
“…Launen et al (20), reported that microorganisms degrade more efficiently PAHs with a lower number of aromatic rings in the molecule. Strains 984 degraded anthracene (64% ± 10%), which possesses 3 aromatic rings, as efficiently as naphthalene, which has 2 aromatic rings (69% ± 10%).…”
Section: Resultsmentioning
confidence: 99%
“…Also, non-ligninolytic fungi, such as Cunninghamella elegans, Penicillium janthinellum, Aspergillus niger and Syncephalastrum sp., are able to transform a variety of PAHs, including chrysene and benzo(a)pyrene, to polar metabolites [13,14,23,24]. These microorganisms carry out a monooxygenation of the PAH molecules by the intracellular cytochrome P-450 dependent oxidase system [25].…”
Section: Introductionmentioning
confidence: 99%